Analysis of the effect of electronic money transactions and macroeconomic variables on economic growth in Indonesia - Sidiq, Sahabudin; Wuryaningtyas, Jannatun Herawati (Jurusan Ilmu Ekonomi, Fakultas Bisnis dan Ekonomika, Universitas Islam Indonesia, 2024)
Purpose – This study aims to analyse the effect of the use of electronic money transactions, money supply, domestic investment, FDI, and labour on economic growth in Indonesia. Methods – The research approach in this study uses quantitative analysis with the Autoregressive Distributed Lag (ARDL) method. Findings – The results showed that the variables of electronic money transactions, money supply, FDI, and labour had significant results on economic growth in Indonesia, while domestic investment showed insignificant results on economic growth in Indonesia. Implication – The government needs to strengthen digital infrastructure and expand access to electronic money to all regions, especially underdeveloped areas, to accelerate financial inclusion. Originality – This study contributes to enriching the literature on the relationship between electronic money and economic growth in developing countries such as Indonesia. AbstrakTujuan – Penelitian ini bertujuan untuk menganalisis pengaruh penggunaan transaksi uang elektronik, jumlah uang beredar, investasi dalam negeri, FDI, dan tenaga kerja terhadap pertumbuhan ekonomi di Indonesia. Metode – Penelitian ini menggunakan analisis kuantitatif dengan metode Autoregressive Distributed Lag (ARDL). Temuan – Hasil Penelitian menunjukkan bahwa variable transaksi uang elektronik, jumlah uang beredar, FDI, dan tenaga kerja menunjukkan hasil yang signifikan terhadap pertumbuhan ekonomi di Indonesia, sedangkan investasi dalam negeri menunjukkan hasil yg tidak signifikan terhadap pertumbuhan ekonomi di Indonesia. Implikasi – Pemerintah perlu memperkuat infrastruktur digital dan memperluas akses uang elektronik ke seluruh wilayah, terutama daerah tertinggal guna mempercepat inklusi keuangan. Orisinalitas – Penelitian ini memberikan kontribusi dalam memperkaya literatur mengenai hubungan antara uang elektronik dan pertumbuhan ekonomi di negara berkembang seperti Indonesia.